The Society for Immunotherapy of Cancer consensus statement on immunotherapy for the treatment of multiple myeloma. Issue 2 (12th July 2020) - Shah, Nina; Aiello, Jack; Avigan, David E; Berdeja, Jesus G; Borrello, Ivan M; Chari, Ajai; Cohen, Adam D; Ganapathi, Karthik; Gray, Lissa; Green, Damian; Krishnan, Amrita; Lin, Yi; et al.
Abstract : Outcomes in multiple myeloma (MM) have improved dramatically in the last two decades with the advent of novel therapies including immunomodulatory agents (IMiDs), proteasome inhibitors and monoclonal antibodies. In recent years, immunotherapy for the treatment of MM has advanced rapidly, with the approval of new targeted agents and monoclonal antibodies directed against myeloma cell-surface antigens, as well as maturing data from late stage trials of chimeric antigen receptor CAR T cells. Therapies that engage the immune system to treat myeloma offer significant clinical benefits with durable responses and manageable toxicity profiles, however, the appropriate use of these immunotherapy agents can present unique challenges for practicing physicians. Therefore, the Society for Immunotherapy of Cancer convened an expert panel, which met to consider the current role of approved and emerging immunotherapy agents in MM and provide guidance to the oncology community by developing consensus recommendations. As immunotherapy evolves as a therapeutic option for the treatment of MM, these guidelines will be updated.